Dynamic Correlations and Volatility Spillovers between Crude Oil and Stock Index Returns: The Implications for Optimal Portfolio Construction - Lee, Yen-Hsien; Huang, Ya-Ling; Wu, Chun-Yu (International Journal of Energy Economics and Policy, 2014)
This paper researches the portfolio construction between stock price of group of seven (G7) and West Texas Intermediate crude oil from January 2, 1998 to March 1, 2012. We investigate the volatility spillover between stock price and oil price with the dynamic conditional correlation (DCC), constant conditional correlation (CCC) and BEKK models, and also analyze their optimal hedge ratio and portfolio weights. The empirical result is that the hedge effectiveness of DCC model is better than the CCC model and BEKK models. The hedge effectiveness (HE) in Canada is the highest but Japan is the lowest. Moreover, the results show that Japan has the biggest optimal portfolio weight and the lowest hedge ratio. We do this research with expectation of providing investors information to increase the basis of investing. Keywords: Crude oil; DCC model; Hedge effectiveness; Optimal portfolio JEL Classifications: C22; G1; N7